Climate risk adaptation and insurance in the Caribbean (CCRIF Grand CaymanKY, 2010)
Presents brief data on the Climate Risk Adaptation and Insurance in the Caribbean Programme which aims to design and implement products between 2011 and 2014 that combine risk reduction and insurance to protect the livelihoods of low income groups in the Caribbean.
Keywords: INSURANCE